Characterization of Biofilms Formed by Foodborne Methicillin-Resistant Staphylococcus aureus - Rodríguez-Lázaro, David; Alonso-Calleja, Carlos; Oniciuc, Elena Alexandra; Capita, Rosa; Gallego, David; González-Machado, Camino; Wagner, Martin; Barbu, Vasilica; Eiros-Bouza, José María; Nicolau, Anca I.; Hernández, Marta (Frontiers in Microbiology, 2018)
The objective of this study was to evaluate the capacity of 49 methicillin resistant Staphylococcus aureus (MRSA) from foods of animal origin (42 from dairy products and 7 from meat and meat products) to form biofilms. Overall, a higher biofilm biomass was observed for those MRSA strains harboring SCCmec type IV, while 8 MRSA strains (5 from dairy products and 3 from meat and meat products) were classified as strong biofilm formers in standard Tryptic Soy Broth medium. When a prolonged incubation period (48h) was applied for those 8 MRSA strains, an increased biofilm biomass accumulation was observed during the time course, whereas the number of viable cells within the biofilms decreased as the biomass increased. The capacity of biofilm production correlated pretty well between the experiments using polystyrene microtiter plates and stainless steel micro-well plates, and significant higher values were observed in stainless steel when glucose was added to TSB during the enrichment. Biofilms were further characterized by confocal laser scanning microscope (CLSM), confirming that proteins and α-polysaccharides were the predominant components inside the extracellular polymeric matrix of biofilms formed by MRSA strains. In conclusion, our results confirm that MRSA isolates from foods of animal origin have significant capacity for forming biofilms with a high protein content, which can play a key role for the successful dissemination of MRSA lineages via food. Knowledge of the capacity of MRSA strains to produce biofilms, as well as characterization of the main MRSA biofilms matrix components, can help both to counteract the mechanisms involved in biofilm formation and resistance and to define more rational control strategies by using tailor-made cleaning agents.